Kemampuan Mendengarkan Drama „Die Räuber“ Karya Friedrich Schiller - Muh. Aslan Pratama Putra; Syamsu Rijal; Syarifah Fatimah (Universitas Negeri Makassar, 2021)
Abstract. This research is descriptive quantitative which aims to determine the ability and factors that influence listening to the drama